Ytterbium Triflate Catalyzed Synthesis of Heterocycles - Sakhuja, Rajeev; Pericherla, Kasiviswanadharaju; Bajaj, Kiran; Khungar, Bharti; Kumar, Anil (Synthesis, 2016)
Ytterbium(III) triflate is an efficient and water-tolerant Lewis acid that has been used as a catalyst for a wide range of organic transformations. Various three-, four-, five-, and six-membered, as well as fused, heterocycles have been synthesized using ytterbium triflate as catalyst in both organic and aqueous solvents. The reaction conditions are relatively mild and the catalyst can be readily recovered from the reaction mixtures to be reused.1 Introduction2 Three-Membered Heterocycles3 Four-Membered Heterocycles4 Five-Membered Heterocycles5 Six-Membered Heterocycles6 Benzo-Fused Heterocycles7 Non-benzenoid Fused Heterocycles8 Spiroheterocycles9 Bridged Heterocycles10 Conclusion
Keywords: lanthanide triflates; ytterbium triflate; Lewis acids; heterocycles